Identification of active metabolites from Gentiana scabra Bunge ethanol-water extract for chicken metatarsal fracture repair - Liu, Yi Jiang; Wang, Yue Min; Jiang, Bin; Luo, Hou Qiang; Liu, Su Zhen; Luo, Shuai (Frontiers in Pharmacology, 2025)
IntroductionFractures are common clinical conditions. Gentiana scabra Bunge extract (GSE) exhibits multiple biological activities, including anti-nociceptive and anti-inflammatory effects. However, its therapeutic effects and active metabolites regarding fracture healing remain poorly understood. In this study, we aimed to investigate the role and active metabolites of GSE in fracture healing by using chicken fracture model.MethodsActive metabolites in GSE were identified and isolated via column chromatography, HPLC, and LC-MS. Fracture repair was assessed by X-ray, and the outcomes were quantified with ImageJ software.ResultsThe results demonstrated that GSE mother liquor and its fractions GSE30, GSE50, GSE70, GSE90 promoted fracture healing. Compared to the control group, the callus area in the GSE group was increased by 1.8-fold on day 3 and by 2.0-fold on day 10. The most favorable healing effect was observed in the GSE50 group, this fraction was primarily composed of gentisin (27.6%), gentiopicroside (7.3%) and isoorientin (65.1%). A notable dose-response relationship was observed between gentisin and isoorientin concentrations in GSE and bone repair outcomes.DiscussionOur findings demonstrate that the active metabolites in GSE are potent agents for accelerating fracture repair. This suggests that gentisin, gentiopicroside and isoorientin is a promising candidate for further preclinical development, and its mechanism of action warrants deeper investigation.